2019
DOI: 10.3390/biomedicines7010006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity and Tolerability of SL-401 (Tagraxofusp): Recombinant Diphtheria Toxin and Interleukin-3 in Hematologic Malignancies

Abstract: Overcoming the leukemia stem cell resistance to intensive chemotherapy has been an area of extensive research over the last two decades. Advances and greater understanding of the molecular biology of leukemia stem cells are in rapid progress. Targeted therapies are currently being used in clinical practice with reasonable response rates, but a cure is being achieved in only a small percentage of patients, most likely due to tumor mutational heterogeneity. A genetically engineered diphtheria toxin fused with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…This might be the reason that FDA approved Ontak® for multiple‐course administration (9 or 18 µg·kg −1 ·day −1 by intravenous infusion over 30–60 min for five consecutive days every 21 days for eight cycles). In December 2018, DT‐based human IL‐3 fusion toxin ELZONRIS™ (tagraxofusp‐erzs; SL‐401; Stemline Therapeutics, Inc., New York, NY, USA) was approved by FDA at 12 µg·kg −1 , intravenously over 15 min once daily on days 1–5 of a 21‐day cycle for multiple consecutive cycles for the treatment of blastic plasmacytoid dendritic cell neoplasm in adult and pediatric patients 2 years and older, in both treatment‐naïve and previously treated populations (Alkharabsheh and Frankel, 2019). We speculate that the CCR4 IT and the bispecific IT could also be administered for multiple‐course treatment of CTCL, as the same truncated diphtheria toxin DT390 was used.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason that FDA approved Ontak® for multiple‐course administration (9 or 18 µg·kg −1 ·day −1 by intravenous infusion over 30–60 min for five consecutive days every 21 days for eight cycles). In December 2018, DT‐based human IL‐3 fusion toxin ELZONRIS™ (tagraxofusp‐erzs; SL‐401; Stemline Therapeutics, Inc., New York, NY, USA) was approved by FDA at 12 µg·kg −1 , intravenously over 15 min once daily on days 1–5 of a 21‐day cycle for multiple consecutive cycles for the treatment of blastic plasmacytoid dendritic cell neoplasm in adult and pediatric patients 2 years and older, in both treatment‐naïve and previously treated populations (Alkharabsheh and Frankel, 2019). We speculate that the CCR4 IT and the bispecific IT could also be administered for multiple‐course treatment of CTCL, as the same truncated diphtheria toxin DT390 was used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ABCG2 has been widely recognized as a promising therapeutic target for eradication of LSCs, since ABCG2 is highly enriched in LSCs and serves a crucial role in the differentiation, proliferation and self-renewal of LSCs (37). Although intensive methods and drugs have been designed to inhibit ABCG2, unfortunately, even with the most advanced treatments to date, the reversal of ABCG2-mediated MDR remains unsatisfactory and the relapse risk of patients with leukemia remains high in the first two years (38). Furthermore, as of yet, appropriate inhibitors of ABCG2 are lacking, since these agents are not very potent or are toxic, and their ability to inhibit ABCG2 has not been verified in patients (4).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that Ontak was efficacious against T cell lymphomas expressing human IL2 receptor CD25 [ 8 ]. Tagraxofusp (Elzonris) is a more recent example of a truncated DT immunotoxin fused with human interleukin 3 (IL-3) which received FDA approval for the treatment of blastic plasmacytoid dendritic cell neoplasm (BPDCN) in 2018 [ 9 ]. Moxetumomab pasudotox (Moxe) is an anti-CD22 immunotoxin that uses truncated Pseudomonas exotoxin as a toxin.…”
Section: Targeted Toxins Have Made a Mark On Cancer Therapymentioning
confidence: 99%